Systems for the management of information in a university context: an investigation of user need. Information systems, Universities, Information strategy - Marcella R.; Knox K. (Information Research: An International Electronic Journal)
The accessibility, reliability, consistency, and relevance of data underpinning information systems are crucial to its use and effectiveness in a university setting. This article reports on the findings of a research project carried out at a new university, which highlighted the role information plays in the success of the operation and in allowing the institution to evolve and meet the challenges posed by the government, students and other stakeholders. Data were gathered from the academic and administrative staff of the university through interviews with senior managers, and a Web-based questionnaire completed by 863 respondents (a 47.9% response rate). The project aimed to explore data and information activities supporting management and strategic decision making in a new university. Project results indicate that there are real deficiencies in the realization of the case institution's information strategy and that these deficiencies must be addressed in developments focusing on improving strategic effectiveness in the future. Particular issues identified included the lack of clarity in responsibility regarding information and concerns about the validity of much of the internally created and maintained data.